Global innovation program for nanoscience education -How can we use electrons for our future, Hydrogen society- - Mitsuomi Yamaguchi; Mitsugu Hamasaki; Masumi Obara; Kozo Obara; Kenji Watanabe (Institut Teknologi Bandung, 2008)
The change of global climate suggests the requirements of new technologies, which can suppress or improve the atmospheric composition. In this paper, we show a revolutionary car technology to decrease CO2. The key is the change of the fuel, from gasoline to hydrogen+H2O. The fuel revolution generates hydrogen economy and induces new scientific targets. Nanoscience and nanotechnology are most expectable tools. Especially, understanding the varieties of characteristics of materials in electronic level is the most important therma. We propose international collaborations on nanoscience education to promote our knowledge and understanding each other.